2007
DOI: 10.1038/ncponc0813
|View full text |Cite
|
Sign up to set email alerts
|

Complete pathological response to bevacizumab and chemoradiation in advanced rectal cancer

Abstract: SUMMARYBackground-Localized rectal cancer responds well to 5-fluorouracil and radiation-based regimens. A phase I-II trial is currently testing the efficacy of adding bevacizumab, a VEGF-specific antibody, to standard chemoradiotherapy. The case presented here is a complete pathological response seen in a patient with extensive and locally invasive carcinoma after receiving this combined treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The same pattern of modulation has been reported for other agents targeting VEGF and VEGFRs (45), but multitargeted inhibitors of class III/V kinase receptors, such as sunitinib, also inhibit sKIT concentrations, reflecting a broader profile of signaling inhibition (34). Preclinical studies have shown that these changes are dose dependent and can correlate with antitumor activity, although they may occur in both naive non-tumor-bearing and tumor-bearing mice (46).…”
Section: Discussionmentioning
confidence: 88%
“…The same pattern of modulation has been reported for other agents targeting VEGF and VEGFRs (45), but multitargeted inhibitors of class III/V kinase receptors, such as sunitinib, also inhibit sKIT concentrations, reflecting a broader profile of signaling inhibition (34). Preclinical studies have shown that these changes are dose dependent and can correlate with antitumor activity, although they may occur in both naive non-tumor-bearing and tumor-bearing mice (46).…”
Section: Discussionmentioning
confidence: 88%
“…In a mouse model, a single dose of Avastin (anti-VEGF antibodies) decreased microvessel density, vessel permeability and interstitial pressure while intratumoral perfusion was improved (Dickson et al 2007). Recent clinical studies support the concept that combining Avastin with chemotherapy can lead to improved outcomes in patients with advanced rectal cancer (Willett et al 2007).…”
Section: Tec Abnormalities May Contribute To Tumor Progressionmentioning
confidence: 80%
“…It is generally recommended that 4 to 6 weeks after bevacizumab be considered the window for operation. Remarkably, Willett et al [4,5] showed surgery performed without any bevacizumab-related surgical complication for patients 7 to 9 weeks after the completion of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on our belief that because bevacizumab poses unique pharmaceutical features, including blockade of tumor angiogenesis and improvement in the delivery of cytotoxic Electronic supplementary material The online version of this article (doi:10.1007/s00464-010-1125-8) contains supplementary material, which is available to authorized users. chemotherapeutic agents by alteration or normalization of the tumor vasculature [4,5], its treatment efficacy may be promising in the context of combination therapy, the central dogma of chemotherapy.…”
mentioning
confidence: 99%